2016
DOI: 10.1186/s12936-016-1294-6
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and genetic differentiation of the normocyte binding protein (nbpxa) of Plasmodium knowlesi clinical isolates from Peninsular Malaysia and Malaysia Borneo

Abstract: BackgroundThe zoonotic malaria parasite Plasmodium knowlesi has become an emerging threat to South East Asian countries particular in Malaysia. A recent study from Sarawak (Malaysian Borneo) discovered two distinct normocyte binding protein xa (Pknbpxa) types of P. knowlesi. In the present study, the Pknbpxa of clinical isolates from Peninsular Malaysia and Sabah (Malaysian Borneo) were investigated for the presence of Pknbpxa types and natural selection force acting on the gene.MethodBlood samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 26 publications
6
48
0
Order By: Relevance
“…This is an interesting finding because the pkmsp7D sequences used in this study is from the same genomic data [24]. Bifurcation of trees, indicating dimorphism and strong negative/purifying selection on invasion genes like DBPαII (PkDBPαII) [31], PkNBPXa [26], PkAMA1 [30] have been reported from clinical samples. This probably indicates that Pkmsp7D is not influenced by geographical origin of the parasite and both the parasite sub-populations were under strong host immune pressure at the central region similar to the non-repeat region in Pkcsp from Malaysia [51].…”
Section: Discussionmentioning
confidence: 89%
“…This is an interesting finding because the pkmsp7D sequences used in this study is from the same genomic data [24]. Bifurcation of trees, indicating dimorphism and strong negative/purifying selection on invasion genes like DBPαII (PkDBPαII) [31], PkNBPXa [26], PkAMA1 [30] have been reported from clinical samples. This probably indicates that Pkmsp7D is not influenced by geographical origin of the parasite and both the parasite sub-populations were under strong host immune pressure at the central region similar to the non-repeat region in Pkcsp from Malaysia [51].…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, it is divergent from clusters 1 and 2, which account for all infections in Malaysian Borneo and apparently a minority of wild macaque infections in peninsular Malaysia. With smaller numbers of samples, recent studies on sequence diversity in genes encoding the normocyte binding protein ( Pknbpxa ) ( 10 ) and the Duffy binding protein ( PkDBP ) ( 30 ), as well as the 18S rRNA gene and the mitochondrial Cox1 gene, have suggested that parasites in peninsular Malaysia had probably diverged from those in Malaysian Borneo.…”
Section: Discussionmentioning
confidence: 99%
“…Human infections in Malaysian Borneo, the portion of Malaysia on the island of Borneo, have divergent genetic subpopulations that are seen in the different macaque species locally, indicating that 2 independent zoonoses may be occurring sympatrically ( 9 ). Noticeable geographic differentiation of parasites between Malaysian Borneo and peninsular Malaysia was also evident in microsatellite analysis; separate studies have revealed divergence between the 2 regions at unlinked genes encoding the normocyte binding protein ( 10 12 ) and the Duffy binding protein ( 13 , 14 ), as well as the 18S rRNA and mitochondrial cytochrome oxidase subunit 1 ( 15 ). Whole-genome sequencing has confirmed the presence of 2 divergent subpopulations of P. knowlesi in Malaysian Borneo and revealed a third divergent cluster of laboratory isolates maintained in laboratories since the 1960s; most of these were recorded to have originated from peninsular Malaysia ( 16 ).…”
mentioning
confidence: 92%
“…It also provides evidence that the two distinct genome dimorphs reflect adaptation to either of the two host macaque species, although no evidence of a complete barrier in primate host susceptibility was found [ 10 ]. A third genome cluster has been described from geographically distinct Peninsular Malaysia [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%